(untitled) (The International Journal of Educational Sciences and Arts, 2026)
This research explores the mental conception of the self in Northern diaspora poetry, focusing on the works of Gibran Khalil Gibran, Mikhail Naimy, and Elia Abu Madi, members of the Pen League. It argues that the experience of exile and cultural estrangement led these poets to reconstruct the concept of the self through the dynamic interaction between mind, body, and human experience. The study adopts Mental Spaces Theory and Mind Schemas Theory as cognitive frameworks to analyze how meaning is generated and how mental imagery is formed within poetic discourse. The analysis reveals that Gibran perceives the self as a spiritual, transcendent entity striving for immortality beyond the physical body; Naimy envisions the self as a musical instrument harmonizing intellect and emotion; while Abu Madi portrays the self through the duality of life and death, embracing the idea of reincarnation and eternal unity with nature. The study concludes that Mahjar poets moved beyond traditional Romanticism toward a philosophical-cognitive vision that situates the self at the center of universal experience. Language in their poetry thus becomes not merely a tool of expression, but a cognitive medium that reveals the psychological and intellectual depth of the self. Consequently, Northern diaspora poetry represents an early model of the intersection between poetic creativity and cognitive thought in modern Arabic literature.